FTIR STUDIES OF THE TEOS/TEVS XEROGEL STRUCTURE USING RAPID THERMAL PROCESSING METHOD - Yanti Mawaddah; Linda Suci Wati; Erdina Lulu Atika Rampun; Anna Sumardi; Aptar Eka Lestari; Zaini Lambri Assyaifi; Muthia Elma (Konversi, 2020)
The tetraethyl orthocycate (TEOS) is mainly used as a silica precursor. Silanol content of silica material is the main cause of low hydrostability which led to resulting in poor performance, especially in water treatment. The stronger bond strength formed by incorporating a carbon structure from triethoxy vinyl silane (TEVS). The xerogel fabrication resulted in the composition of TEOS: TEVS: EtOH: HNO3: H2O: NH3 to be 0.9: 0.1: 38: 0.00078: 5: 0.0003.   . The purpose is to study the structure of organosilica xerogel calcined at 350oC, 450oC and 600oC in the Fourier-transform infrared (FTIR) using rapid thermal processing. The deconvolution of FTIR spectra calculated using the Fityk software. The result of the best xerogel peak shows at calcination of 450°C with peak area siloxane of 15.39, silanol of 3.32 and silica carbon of 3.85.